KEUNTUNGAN DAN KERUGIAN PEMAKAIAN TENAGA OUSEARCHING SEKURITI DI LINGKUNGAN SEKOLAH YOS SUDARSO - BATAM - Laurensius D Sanga (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Yos Sudarso School is under the Tunas Karya Foundation belonging to the Catholic Church of the Pangkalpinang Diocese. Yos Sudarso School is in the Batam-Riau Archipelago area. It has an integrated campus located in the Batam center area which consists of Kindergarten to Public High School. It also has thousands of students and hundreds of teachers and other employees. Of course this dense environment must be maintained in order to avoid things that are not desirable. On that basis, the school has implemented an outsearching system for security personnel. Many conveniences are obtained from this system. For this reason, the authors conducted research using qualitative methods to determine the advantages and disadvantages of implementing this system. Among them, it was found that the school received many advantages, including special skills, cost efficiency, focus on the core business, and flexibility. Although there are still some disadvantages to be gained.Keywords: Outsearching, Yos Sudarso School, Advantages and Disadvantages.